BALANCE SCORECARD SEBAGAI PENGUKURAN KINERJA PADA PERGURUAN TINGGI - Umaimah Umaimah (Jurnal Manajerial, 2019)
The purpose of this study was to analyze the performance of the university with the balanced scorecard. This study was included in the category of qualitative research.The results showed, based on measurements of four perspectives; growth and learning, internal business processes, customers, and finance, the university has done a good performance so apparent value increased in a positive ROI.